Pemahaman Tentang Seksualitas pada Anak Usia Dini Melalui Aktivitas Membacakan Cerita - Yudho Bawono (Universitas Trunojoyo Madura, 2014)
Terms of sexuality can be understood as something related to sex. Included is the value, orientation and sexal behavior and not merely biological sex organs. The meaning of the term sexuality it self can be achieved in the form of an understanding of sexuality in children from an early age. One form is through the activity of reading a story, which is a fun activity to do if there is an interaction between the giver story with hearer story. The media that can be used by the giver is to read a story book reading. Bunanta (2008) is reading book which can be read by the child and which are labeled sexually explicit, that is given openly that need adult assistance,must be considered apparent. Most other experts recommend that although the issue of sexuality conveyed implicitly, better parents read the book first. Through this activity, children can be told about the characters and the stories from the original story. Through these activities the children are not anly taught about everything related to biological sex organs, but also the value, orientation, and sexual behavior (Bawono, 2014)